Nova Tangelo - Stephen H. Futch; L.K. Jackson (EDIS)
This document is about the Nova Tangelo. This is a hybrid of Clementine tangerine crossed with Orlando tangelo that was released in 1964 by the U.S. Department of Agriculture. This is the same cross that produced the Robinson, Osceola and Lee tangerines.